SISTEM CERDAS IRIGASI MENGGUNAKAN METODE FUZZY LOGIC PADA TANAMAN TOMAT - Juliarni Pogasang; Gunawan Gunawan; La Surimi (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2024)
This study designs an IoT-based intelligent irrigation system using Fuzzy Logic to manage tomato plant watering. The system monitors soil moisture and temperature in real-time, automating irrigation to optimize water usage based on plant needs. Using the Fuzzy Sugeno method, it combines moisture and temperature data to determine watering duration. Key components include sensors, a microcontroller, an IoT module integrated with the Blynk app, and an automatic water pump. Testing shows the system functions effectively, detecting environmental changes with a 0.47% deviation from manual methods and achieving a 99.50% automation success rate.